Biofilm Formation among Clinical and Food Isolates of Listeria monocytogenes. (29th December 2013) - Barbosa, Joana; Borges, Sandra; Camilo, Ruth; Magalhães, Rui; Ferreira, Vânia; Santos, Isabel; Silva, Joana; Almeida, Gonçalo; Teixeira, Paula
Abstract : Objective . A total of 725 Listeria monocytogenes isolates, 607 from various foods and 118 from clinical cases of listeriosis, were investigated concerning their ability to form biofilms, at 4°C during 5 days and at 37°C during 24 h. Methods . Biofilm production was carried out on polystyrene tissue culture plates. Five L. monocytogenes isolates were tested for biofilm formation after being exposed to acidic and osmotic stress conditions. Results . Significant differences (P < 0.01 ) between clinical and food isolates were observed. At 37°C for 24 h, most food isolates were classified as weak or moderate biofilm formers whereas all the clinical isolates were biofilm producers, although the majority were weak. At 4°C during 5 days, 65 and 59% isolates, from food and clinical cases, respectively, were classified as weak. After both sublethal stresses, at 37°C just one of the five isolates tested was shown to be more sensitive to subsequent acidic exposure. However, at 4°C both stresses did not confer either sensitivity or resistance. Conclusions . Significant differences between isolates origin, temperature, and sublethal acidic stress were observed concerning the ability to form biofilms. Strain, origin, and environmental conditions can determine the level of biofilm production by L. monocytogenes isolates.